Methodological considerations for large-scale breath analysis studies: lessons from the U-BIOPRED severe asthma project. (30th October 2018) - Ahmed, Waqar M; Brinkman, Paul; Weda, Hans; Knobel, Hugo H; Xu, Yun; Nijsen, Tamara M; Goodacre, Royston; Rattray, Nicholas; Vink, Teunis J; Santonico, Marco; Pennazza, Giorgio; Montuschi, Paolo; et al.
Abstract: Methods for breath sampling and analysis require robust quality assessment to minimise the risk of false discoveries. Planning large-scale multi-site breath metabolite profiling studies also requires careful consideration of systematic and random variation as a result of sampling and analysis techniques. In this study we use breath sample data from the recent U-BIOPRED cohort to evaluate and discuss some important methodological considerations such as batch variation and correction, variation between sites, storage and transportation, as well as inter-instrument analytical differences. Based on this we provide a summary of recommended best practices for new large scale multi-site studies.